Proceedings of the 25th International Congress of Mechanical Engineering 2019
DOI: 10.26678/abcm.cobem2019.cob2019-1306
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Atomization by Impinging Jets of Liquid and Gelled Green Propellants

Abstract: Gelled propellants are an interesting option for rockets and missiles propulsion systems, since they combine high performance with facility of handling and storage. These characteristics are due to the shear thinning non-Newtonian behavior of gels. High shear rates can lead to extensive liquefaction of gelled fluids. This liquefaction offers the possibility to develop engines that can be throttled like liquid propellant engines. Impinging jet injectors are commonly used in propulsion systems applications since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The sheet regimes goes from stable closed sheet (u = 2.81 m/s) to impact wave regime (u = 7.36 and 12.45 m/s). According to Dias et al (2019b), stable closed rim for hydrous ethanol can be found until the Reynolds of jet reaches a value around 1700, considering the designed injector. Impact waves starts from the impingement point and grow in amplitude as the distance from the impingement point increase, as seen for u = 4.89 m/s.…”
Section: Free Jet and Sheet Visualizationmentioning
confidence: 99%
“…The sheet regimes goes from stable closed sheet (u = 2.81 m/s) to impact wave regime (u = 7.36 and 12.45 m/s). According to Dias et al (2019b), stable closed rim for hydrous ethanol can be found until the Reynolds of jet reaches a value around 1700, considering the designed injector. Impact waves starts from the impingement point and grow in amplitude as the distance from the impingement point increase, as seen for u = 4.89 m/s.…”
Section: Free Jet and Sheet Visualizationmentioning
confidence: 99%